El uso progresivo de la fuerza y su incidencia en el CRS Cotopaxi - transitoria - Calero Laverde, Wilmer Orlando (2024)
The progressive use of force is a mechanism used in deprivation of liberty centers to maintain order by the National Police in the company of the Armed Forces in compliance with their duties and obligations emanating from the Constitution of the Republic of Ecuador. However, when the institutions in charge of maintaining order abuse their power, they violate the constitutional rights of those deprived of liberty, mainly they violate the right to life and consequently the right to personal integrity, which is why they must be complied with. with certain parameters and principles, among which are established: legality, absolute necessity, proportionality and humanity. In this way, the progressive use of force has a positive impact on the center of deprivation of liberty because it allows the institutions in charge of maintaining order not to abuse their power and in turn not violate the rights of those deprived of liberty. Therefore, surveys were applied showing that the progressive use of force does not violate the human rights of those deprived of liberty, considering that life and personal integrity are considered the main rights that are protected. At the same time, the ruling in case 33-20.IN and accumulated was developed, highlighting the unconstitutionality of the form of Agreement 179 due to the non-compliance with the principle of legal reserve, the incompetence in matters of material on the part of the Minister of the Interior when issuing the agreement. and the unconstitutionality of the Public and State Security Law as it is contrary to what is established in article 158 of the Constitution of the Republic of Ecuador.